2016
DOI: 10.1017/s0033291716002749
|View full text |Cite
|
Sign up to set email alerts
|

Performance characteristics and clinical utility of diagnostic criteria proposals in bereaved treatment-seeking patients

Abstract: Both proposed DSM-5 criteria for PCBD and criteria for PGD appear to be too restrictive as they failed to identify substantial numbers of treatment-seeking individuals with clinically significant levels of grief-related distress and impairment. Use of CG criteria or a similar algorithm appears to be warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
40
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 26 publications
1
40
0
2
Order By: Relevance
“…Several different statistical methods have been used to confirm the distinct nature of PGD, including confirmatory factor analysis (Boelen, van den Hout, & van den Bout, 2008), latent class analysis (Boelen, Reijntjes, J. Djelantik, & Smid, 2016) and network analysis (Robinaugh, LeBlanc, Vuletich, & McNally, 2014). In light of recent research (Cozza et al, 2016; Mauro et al, 2017), it should be noted that different results have been reported in terms of the diagnostic performance of the PGD-2009 criteria, presumably depending on the study population sample. For example, the original paper (Prigerson et al, 2009) assessed the PGD-2009 in a community sample in the USA, whereas the more recent reports from Cozza et al (2016) and Mauro et al (2017) assessed military and clinical samples and found differing rates of diagnostic sensitivity.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Several different statistical methods have been used to confirm the distinct nature of PGD, including confirmatory factor analysis (Boelen, van den Hout, & van den Bout, 2008), latent class analysis (Boelen, Reijntjes, J. Djelantik, & Smid, 2016) and network analysis (Robinaugh, LeBlanc, Vuletich, & McNally, 2014). In light of recent research (Cozza et al, 2016; Mauro et al, 2017), it should be noted that different results have been reported in terms of the diagnostic performance of the PGD-2009 criteria, presumably depending on the study population sample. For example, the original paper (Prigerson et al, 2009) assessed the PGD-2009 in a community sample in the USA, whereas the more recent reports from Cozza et al (2016) and Mauro et al (2017) assessed military and clinical samples and found differing rates of diagnostic sensitivity.…”
Section: Introductionmentioning
confidence: 91%
“…In light of recent research (Cozza et al, 2016; Mauro et al, 2017), it should be noted that different results have been reported in terms of the diagnostic performance of the PGD-2009 criteria, presumably depending on the study population sample. For example, the original paper (Prigerson et al, 2009) assessed the PGD-2009 in a community sample in the USA, whereas the more recent reports from Cozza et al (2016) and Mauro et al (2017) assessed military and clinical samples and found differing rates of diagnostic sensitivity. This attests to the importance of establishing future diagnostic criteria across a variety of samples.…”
Section: Introductionmentioning
confidence: 91%
“…Core symptoms of CG include intense yearning or longing for the deceased, sorrow or emotional pain, and preoccupation with thoughts about the death or the deceased (Simon et al, ). Additional symptoms include difficulty accepting the death, avoidance of reminders of the deceased or of the permanence of the loss, difficulty planning for the future, role and identity confusion, feeling that life is unbearable without the deceased, and a wish to die to join the deceased (Mauro et al, ; Simon et al, ). Although CG shares many similar symptoms with other stress‐related disorders, such as PTSD and MDD, it also includes symptoms that are not observed in PTSD or MDD, and CG can occur independently of these conditions (Bonanno et al, ; Simon, ).…”
Section: Introductionmentioning
confidence: 99%
“…shown that current proposed criteria may not sufficiently capture all clinical cases of persistent complex bereavement disorder (Cozza et al, 2016), there is also a lack of consensus of the time course of disabling grief and the timing of treatment (Shear, 2015). DSM-5 requires symptom duration of 12 months for diagnosis, whereas studies of complicated grief consider criterion duration of 6 months and show bene-fit early in the course from grief-specific psychotherapy (Mauro et al, 2017;Shear, Frank, Houck, & Reynolds, 2005). The current study was unable to examine grief disorders as an outcome, but showed that depression and anxiety (typically comorbid with grief) onset within 6 months of the loss and persist for 1 year.…”
Section: Discussionmentioning
confidence: 99%